2020
DOI: 10.1016/j.ibmb.2020.103497
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of the orco odorant receptor co-receptor impairs olfactory function in the malaria vector Anopheles coluzzii

Abstract: Mosquitoes rely heavily on their olfactory systems for host seeking, selection of oviposition sites, and avoiding predators and other environmental dangers. Of these behaviors, the preferential selection of a human blood-meal host drives the vectorial capacity of anthropophilic female Anopheles coluzzii mosquitoes. Olfactory receptor neurons (ORNs) are dispersed across several appendages on the head and express an obligate odorant receptor co-receptor (Orco) coupled with a "tuning" odorant receptor (OR) to for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 57 publications
1
48
1
Order By: Relevance
“…In insects, in addition to individual Ors that are responsible for recognizing specific odorants, an obligate co-receptor (Orco) is required for detection of diverse odorants 28 30 and can be used to infer whether insect attraction or avoidance response is Or-mediated. No obvious degenerate DAPI-stained ORNs were detected from orco −/− Anopheles mosquitoes 31 . We found that pyrethrum repellency was significantly reduced in orco −/− Ae.…”
Section: Resultsmentioning
confidence: 88%
“…In insects, in addition to individual Ors that are responsible for recognizing specific odorants, an obligate co-receptor (Orco) is required for detection of diverse odorants 28 30 and can be used to infer whether insect attraction or avoidance response is Or-mediated. No obvious degenerate DAPI-stained ORNs were detected from orco −/− Anopheles mosquitoes 31 . We found that pyrethrum repellency was significantly reduced in orco −/− Ae.…”
Section: Resultsmentioning
confidence: 88%
“…Indeed, it has been shown to be a potent attractant for anopheline larvae and specifically recognized by Or2 and Or10, both of which are expressed in the larval antennae ( Xia et al, 2008 ). Lastly, the inhibitory responses to several volatiles uncovered by orco −/− mutant sensory cones ( Sun et al, 2020 ) and the inhibition of background spiking, as well as the relative sparsity of excitatory responses characteristic of D, E, and F group neurons reported here, may, in part, reflect the impact of ephaptic interactions between neurons ( Figure 4 ) within the closely packed chemosensory neurons of the larval antennae, as has been observed in Drosophila ORNs ( Su et al, 2012 ).…”
Section: Discussionmentioning
confidence: 52%
“…Previous work has established the critical role of the OR co-receptor (Orco) in the chemical ecology and OR-dependent olfactory responses of An. coluzzii larvae ( Sun et al, 2020 ; Liu et al, 2010 ). To begin with, we examined the background neuronal activity across the larval sensory cone in orco −/− mutant larvae in which background activity, as well as the responses to 2-methylphenol and acetophenone and 72 other volatiles, were dramatically reduced relative to wild-type controls ( Figures 7A and 7B ) ( Sun et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations